Gender Mainstreaming through Women’s Enterpreneurship: Insights from Women’s Empowerment and Child Protection Office in Tanjungpinang City - Desvia Silvana; Indah Meilana Panjaitan; Puja Lestari Manurung (UIN Siber Syekh Nurjati Cirebon, 2024)
This study examines the role of gender mainstreaming in the implementation of entrepreneurship training programs conducted by the Women’s Empowerment and Child Protection Office in Tanjungpinang City. The program aims to empower women, particularly those from vulnerable backgrounds, by enhancing their skills, fostering self-confidence, and promoting gender equality. This qualitative study utilizes interviews, observations, and documentation as data collection techniques, with training participants and program facilitators serving as primary informants. The findings reveal that the program integrates gender mainstreaming principles by providing practical skill training, such as sewing and baking, alongside knowledge in digital marketing, financial management, and risk management. The initiative has been effective in equipping participants to manage micro, small, and medium enterprises (MSMEs), while also enhancing their economic independence and family welfare. However, the study also identifies challenges, such as participants’ entrenched patriarchal mindsets and limited support from families or communities. To address these barriers, the program emphasizes community-based approaches and includes follow-up mentoring to ensure sustainability. Overall, this study highlights the significant positive impact of entrepreneurship training on women’s empowerment and underscores its strategic role in advancing gender equality and local economic development.